Engineering of the Stellarator of Costa Rica: SCR-1 - Piedra, C.; Jiménez, W.; Esquivel, L.; Esquivel, R.; Sánchez, K.; González, J.; Mora-Meléndez, Jaime; Otárola-Zúñiga, Carlos; Vargas-Blanco, Iván (Institute of Physics Publishing, 2015)
This Paper aims at briefly describing the challenge of the design and construction of the Stellarator of Costa Rica 1 (SCR-1) [1]. The SCR-1 is a small modular Stellarator for magnetic confinement of plasma (Ro=0.238 m, =0.059 m, Ro/a>4.0, expected plasma volume ≈ 0.016 m3, 10 mm thickness 6061-T6 aluminum vacuum vessel) developed by the Plasma Laboratory for Fusion Energy and Applications of the Instituto Tecnológico de Costa Rica (ITCR).
https://www.scopus.com/inward/record.url?eid=2-s2.0-84938149517&partnerID=40&md5=9fd63fd2eb1657d79d29405b7e023cdd
Keywords: Plasma; Diseño; Construcción; Vacunas; Research Subject Categories::TECHNOLOGY::Engineering physics::Plasma physics with fusion